ANTIDEPRESSANT PROPERTIES OF AQUEOUS MACERATE FROM GLADIOLUS DALENII CORMS - Ngoupaye, Gwladys Temkou; Bum, Elisabeth Ngo; Taiwe, Germain Sotoing; Moto, Fleur Clarisse Okomolo; Talla, Emmanuel (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Background: Gladiolus dalenii Van Geel (Iridaceae) has been used for the treatment of depression and psychotic disorders in African traditional medicine. The aim of this study was to assess the effect of the aqueous extract from the corm of Gladiolus dalenii and its possible mechanisms of action. Materials and Methods: We assessed the antidepressant properties of G. dalenii corm aqueous extract in mice, using the open field, forced swimming, and tail suspension tests. Spontaneous locomotor activity of mice given various doses of G. dalenii extract (per os) was determined in the open field, whereas immobility was evaluated in the other two tests. Results: Extract maximal effect was observed at 15 mg/kg, as mice displayed a marked reduction in immobility time in both the forced swimming test (80%) and the tail suspension test (66%). In further studies aimed at investigating the mechanism of action of G. dalenii extract, the latter significantly antagonized the effect of N-methyl-D- aspartate (NMDA, 75 mg/kg) at both the doses 15 mg/kg (p<0.001) and 150 mg/kg (p=0.004). A significant reduction in immobility time was also observed following treatment with combinations of a sub-effective dose of extract (7.5 mg/kg) with either the NMDA receptor antagonist D-(-)-2-amino-7-phosphonoheptanoic acid (D-AP7, 50 mg/kg, P< 0.001), the serotonin reuptake inhibitor fluoxetine (5 and 10 mg/kg, P< 0.001and P< 0.001 respectively), and the multi-target antidepressant imipramine (5 and 10 mg/kg, P< 0.001and P< 0.001 respectively). Moreover, neither G. dalenii extract alone nor its combinations with NMDA ligands imipramine and fluoxetine enhanced mouse spontaneous locomotor activity. Conclusion: Altogether, these results suggest that G. dalenii has antidepressant properties, probably mediated through interactions with NMDA, serotonin and/ or noradrenergic systems, and may justify its use in traditional medicine.